KONSEPSI ETIKA, MORAL, DAN ILMU PENGETAHUAN DALAM PERSPEKTIF HUMANISME - Asrulla Asrulla; Ahmad Syukri; Maryani; Firdaus Jeka; Roni Junaidi (LPPM Universitas Cipta Mandiri, 2024)
The science seeks to reveal reality as it is; ethics and morals are essentially guides on what humans should do. Science is a conscious effort to investigate, discover, and enhance human understanding of various aspects of reality within the human realm. These aspects are limited to produce definite formulations. Science provides certainty by limiting its scope of view, and the certainty of sciences is derived from its limitations. Science is not just knowledge but encompasses a collection of knowledge based on agreed-upon theories and can systematically be tested with a set of recognized methods in a specific field of science.